Ekranisasi Alur Manhwa dan Anime Solo Leveling Karya Chu-Gong - Ramanda, Satryo (PT. Alahyan Publisher Sukabumi, 2024)
Ecranization is the adaptation of narrative literary works into films. Therefore, this research aims to discuss the process of adapting Chu-Gong's Solo Leveling manhwa into anime form with the main focus of the research being to analyze changes in the storyline that occurred in the adaptation process. This research is qualitative research using comparative descriptive methods. This research compares the storyline with the data source, namely footage from the manhwa Solo Leveling chapters 1-26 and the anime Solo Leveling episodes 1-6. Apart from that, this research uses a documentation data collection method. The results showed that there were two main types of changes in the storyline: additions and varied changes. Six examples of additional plots and three examples of varied changes were found. These changes aim to adapt the story to the anime format, fill in plot gaps, and make the narrative more structured.